Enhanced renewal of regulatory T cells in relation to CD4+ conventional T lymphocytes in the peripheral compartment. Issue 2 (17th December 2015) - Nogueira, Jeane de Souza; Canto, Fábio Barrozo do; Nunes, Caroline Fraga Cabral Gomes; Vianna, Pedro Henrique Oliveira; Paiva, Luciana de Souza; Nóbrega, Alberto; Bellio, Maria; Fucs, Rita
Summary: CD4 + Foxp3 + regulatory T (Treg) cells are necessary for the maintenance of self‐tolerance and T‐cell homeostasis. This population is kept at stable frequencies in secondary lymphoid organs for the majority of the lifetime, despite permanent thymic emigration or in the face of thymic involution. Continuous competition is expected to occur between recently thymus‐emigrated and resident Treg cells (either natural or post‐thymically induced). In the present work, we analysed the renewal dynamics of Treg cells compared with CD4 + Foxp3‐ conventional T cells (Tconv), using protocols of single or successive T‐cell transfers into syngeneic euthymic or lymphopenic ( nu/nu or RAG2 −/− ) mice, respectively. Our results show a higher turnover for Treg cells in the peripheral compartment, compared with Tconv cells, when B cell‐sufficient euthymic or nude hosts are studied. This increased renewal within the Treg pool, shown by the greater replacement of resident Treg cells by donor counterparts, correlates with augmented rates of proliferation and is not modified following temporary environmental perturbations induced by inflammatory state or microbiota alterations. Notably, the preferential substitution of Treg lymphocytes was not observed in RAG2 −/− hosts. We showed that limited B‐cell replenishment in the RAG2 −/− hosts decisively contributed to the altered peripheral T‐cell homeostasis. Accordingly, weekly transfers of B cells to RAG2 −/− hosts rescued the preferential substitution of Treg lymphocytes. Our study discloses a new aspect of T‐cell homeostasis that depends on the presence of B lymphocytes to regulate the relative incorporation of recently arrived Treg and Tconv cells in the peripheral compartment.